Amyloid load in Parkinson's disease dementia and Lewy body dementia measured with [11C]PIB positron emission tomography. Issue 12 (24th July 2008) - Edison, P; Rowe, C C; Rinne, J O; Ng, S; Ahmed, I; Kemppainen, N; Villemagne, V L; O'Keefe, G; Någren, K; Chaudhury, K R; Masters, C L; Brooks, D J
Abstract : Background: Neuropathological studies have reported varying amounts of amyloid pathology in dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD). [11C]PIB positron emission tomography (PET) is a marker of brain amyloid deposition. The aim of this study was to quantify in vivo amyloid load in DLB and PDD compared with control subjects and subjects with Parkinson's disease (PD) without dementia. Methods: 13 DLB, 12 PDD, 10 PD subjects and 41 age matched controls (55–82 years) were recruited. Each subject underwent clinical evaluation, neuropsychological assessment, T1 and T2 MRI, and [11C]PIB PET. The amyloid load was estimated from 60–90' target region:cerebellar [11C]PIB uptake ratios. Object maps were created by segmenting individual MRIs and convolving them with a probabilistic atlas. Cortical [11C]PIB uptake was assessed by region of interest analysis. Results: The DLB cohort showed a significant increase in mean brain [11C]PIB uptake and individually 11 of the 13 subjects with DLB had a significantly increased amyloid load. In contrast, mean [11C]PIB uptake was normal for the PDD group although two of 12 patients with PDD individually showed a raised amyloid load. Where significant increases in [11C]PIB uptake were found, it was increased in cortical association areas, cingulate and striatum. None of the subjects with PD showed significantly raised cortical [11C]PIB uptake. Conclusion: This study suggests that amyloid load is significantly raised in over 80% of subjects with DLB, while amyloid pathology is infrequent in PDD. These in vivo PET findings suggest that the presence of amyloid in DLB could contribute to the rapid progression of dementia in this condition and that anti-amyloid strategies may be relevant.